2013
DOI: 10.1007/s10967-013-2808-0
|View full text |Cite
|
Sign up to set email alerts
|

Uranium concentration in blood samples of Southern Iraqi leukemia patients using CR-39 track detector

Abstract: The simple and effective technique of fission track etch has been applied to determine trace concentration of uranium in human blood samples taken from two groups of male and female participants: leukemia patients and healthy subjects group. The blood samples of leukemia patients and healthy subjects were collected from three key southern governorates namely, Basrah, Muthanna and Dhi-Qar. These governorates were the centers of intensive military activities during the 1991 and 2003 Gulf wars, and the discarded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 19 publications
(25 reference statements)
1
22
1
Order By: Relevance
“…The average uranium content in human soft tissues in this study is higher than published values with other researchers [31][32][33]. The cause behind such results can be attributed to the high levels of uranium contamination in the region of southern Iraq as a result of military activities during the Gulf Wars which led to the exposure of individuals to high levels of radioactive pollution [1,2]. From Table 2, it was found that observed uranium concentrations in kidney were widely scattered and the average uranium concentration (6.51 lg kg -1 ) for abnormal tissues and (4.11 lg kg -1 ) for normal tissues was higher than those in the other abnormal and normal soft tissues, because the kidney is one of the principle sites of uranium deposition in the body [34].…”
Section: Resultscontrasting
confidence: 69%
See 3 more Smart Citations
“…The average uranium content in human soft tissues in this study is higher than published values with other researchers [31][32][33]. The cause behind such results can be attributed to the high levels of uranium contamination in the region of southern Iraq as a result of military activities during the Gulf Wars which led to the exposure of individuals to high levels of radioactive pollution [1,2]. From Table 2, it was found that observed uranium concentrations in kidney were widely scattered and the average uranium concentration (6.51 lg kg -1 ) for abnormal tissues and (4.11 lg kg -1 ) for normal tissues was higher than those in the other abnormal and normal soft tissues, because the kidney is one of the principle sites of uranium deposition in the body [34].…”
Section: Resultscontrasting
confidence: 69%
“…After the irradiation, the CR-39 detectors were etched under controlled conditions in NaOH etchant solution as reported elsewhere [1][2][3]. The fission tracks density was recorded using the optical microscope at a magnification of 4009.…”
Section: Experimental Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed, for example, increased incidences of various types of cancer and birth defects among civilians living in those affected areas [60][61][62][63][64][65][66]. These studies suggest that DU exposure is either a primary cause or related to the main cause of congenital anomalies and increased rates of cancer.…”
Section: Epidemiologic Studymentioning
confidence: 99%